Protective Effect of Resveratrol against Hexavalent Chromium-Induced Genotoxic Damage in Hsd:ICR Male Mice - Tonancy Nicolás-Méndez; Sam Kacew; Alda Rocío Ortiz-Muñiz; Víctor Manuel Mendoza-Núñez; María del Carmen García-Rodríguez (Molecules, 2022)
The aim of this study is to examine the ability of resveratrol to counteract hexavalent chromium [Cr(VI)]-induced genetic damage, as well as the possible pathways associated with this protection. Hsd:ICR male mice are divided into groups of the following five individuals each: (a) control 1, distilled water; (b) control 2, ethanol 30%; (c) resveratrol, 50 mg/kg by gavage; (d) CrO3, 20 mg/kg intraperitoneally; (e) resveratrol + CrO3, resveratrol administered 4 h prior to CrO3. The assessment is performed on peripheral blood. Micronuclei (MN) kinetics are measured from 0 to 72 h, while 8-hydroxydeoxyguanosine (8-OHdG) adduct repair levels, endogenous antioxidant system biomarkers, and apoptosis frequency were quantified after 48 h. Resveratrol reduces the frequency of Cr(VI)-induced MN and shows significant effects on the 8-OHdG adduct levels, suggesting that cell repair could be enhanced by this polyphenol. Concomitant administration of resveratrol and Cr(VI) results in a return of the activities of glutathione peroxidase and catalase to control levels, accompanied by modifications of superoxide dismutase activity and glutathione levels. Thus, antioxidant properties might play an important role in resveratrol-mediated inhibition of Cr(VI)-induced oxidant genotoxicity. The increase in apoptotic cells and the decrease in necrosis further confirmed that resveratrol effectively blocks the actions of Cr(VI).